The Determinant Factors of the Public Open Space Activity in Patukan Rail-Station Area, Sleman, Yogyakarta - Bekti Sulistya; Tarcicius Yoyok Wahyu Subroto (Built Environment Studies, 2022)
The phenomenon of public open space activity in Patukan railroad area is a spatial problem related to the behavior of its users. Residents around Patukan railway station use the railroad crossing area as a place to gather, culinary tours and recreation while watching train activities that pass in the afternoon. Activities that occur in the area raise concerns about the security and safety of visitors who are active there considering that the majority of visitors carry out these activities on railroad tracks. PT. Indonesian Railways (KAI) Daop VI Yogyakarta as the manager of Patukan railway station has banned any activity in the area, but the regulation is still not effective enough to prevent people from gathering in that area. This study aims to identify the phenomenon of activity that occurs in the Patukan railway station area and to determine the factors that cause the setting of public open space activities in that area by using a qualitative and quantitative method based on rationalism. Based on the results of the study it is known that there are factors that cause the setting of public open space activities in the area consisting of perception, time, environmental and spatial factors that support activity actors to carry out activities there.